PENGARUH APLIKASI QUIZIZZ TERHADAP HASIL BELAJAR IPA KELAS VII SMP NEGERI 2 PANCA RIJANG KABUPATEN SIDENDRENG RAPPANG - Saripaini; Abdul Kahar; Madaling (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study uses a type of experimental research with a true experiment research design. The population in the study was 70 students and the sample was 23 seventh grade students who were then divided into 2 groups, namely the treatment group  with  the  Quizizz  application  and  the  control  group  with  conventional  methods.  The  data analysis technique used is the mean formula. The results showed that student learning outcomes using the Quizizz application obtained a total score of 757 with an average student score of 75,7. While in the control group students with conventional methods obtained a total student score of 812 with an average student score of 62,5. So it can be concluded that learning with the Quizizz Application is  more effective than conventional methods on Science Learning Outcomes of Class VII SMP Negeri 2Panca Rijang Sidendreng Rappang Regency.